Childhood Trauma and Social Support: Effects on Treatment Compliance in Gender Dysphoria - Çavuş Uysal, Ayten; Durcan, Emre; Uysal, Serhat; Sulu, Cem; Turan, Şenol; Kadıoğlu, Pınar (Cerrahpaşa Medical Journal, 2024)
Objective: To assess the sociodemographic, clinical, and psychiatric characteristics of individuals with gender dysphoria (GD) and the impact of these characteristics on treatment compliance. Methods: All individuals with GD who were admitted to the clinic for endocrinological treatment were asked to participate in this cross-sectional study. Individuals with GD who came for control every three months in the first year and every six months from the second year were regarded as “regularly followed,” and those who did not comply were regarded as “loss to follow-up.” The GD group was also paired with age-matched cisgender male and female volunteers. Data regarding the individuals’ Gender-Affirming Treatment processes were obtained retrospectively from medical charts. All participants were asked to complete the Social Adaptation Self-evaluation Scale, childhood trauma questionnaire (CTQ), and Multidimensional Scale of Perceived Social Support. Results were compared between groups. Results: This study included 50 individuals with GD who were assigned female at birth (AFAB-GD), 50 individuals with GD who were assigned male at birth (AMAB-GD), 28 cis-males, and 48 cis-females. AMAB-GD had higher CTQ, emotional, and sexual abuse scores than AFAB-GD (P = .04; P = .03; P = .012; respectively). The rate of regular follow-up was higher for AFAB-GD (n = 48, 77.1%) than AMAB-GD (n = 39, 56.4%) (P = .04). Among GD individuals who missed follow-up sessions, AMAB-GD (n = 17, 64.7%) had higher suicide rates than AFAB-GD (n = 11, 9.1%) (P = .004). Conclusions: Childhood trauma, particularly in the subcategories of emotional and sexual abuse, may be some of the reasons why AMAB-GD fail to follow up and comply with treatment. Cite this article as: Çavuş Uysal A, Durcan E, Uysal S, Sulu C, Turan Ş, Kadıoğlu P. Childhood trauma and social support: effects on treatment compliance in gender dysphoria. Cerrahpaşa Med J. 2024;48(3):253-258.